Regime térmico e hídrico do solo para área de floresta tropical em anos de El Niño e La Niña, Caxiuanã-PA: estudo de caso - SANTOS, Sergio Rodrigo Quadros dos (2015)
The thermal and hydrologic regime to soil if behave differently in years of occurrence of El Niño, La Niña and that non-occurrence about both (El Niño and La Niña). To study these behaviors, we used data of the hourly total and monthly of rainfall, average hourly and monthly data of soil temperature at depths of 2 cm and 10 cm and soil moisture at depths of 5cm and 20cm, for years the events searched. The results show that the year was about the influence of El Niño had higher temperature and lower values of soil moisture when compared with the year that was on the influence of La Niña. On the other hand the years that there is no occurrence of the phenomena El Niño and La Niña, showed values of soil temperature (moisture) higher (smaller) than the La Niña year, but smaller (higher) than the year of El Niño.